An Adaptive Sorting Algorithm for Almost Sorted List - Damdoo, Rina; Kalyani, Kanak (International Journal of Computer Sciences and Engineering, 2025)
Sorting algorithm has a great impact on computing and also attracts a grand deal of research. Even though many sorting algorithms are evolved, there is always a scope of for a new one. As an example, Bubble sort was first analyzed in 1956, but due to the complexity issues it was not wide spread. Although many consider Bubble sort a solved problem, new sorting algorithms are still being evolved as per the problem scenarios (for example, library sort was first published in 2006 and its detailed experimental analysis was done in 2015) [11]. In this paper new adaptive sorting method Paper sort is introduced. The method is simple for sorting real life objects, where the input list is almost but not completely sorted. But, one may find it complex to implement when time-and-space trade-off is considered.